Dopplerfluxometria da artéria femoral de cães adultos hígidos (Canis lupus familiaris) - dos Santos, Ivan Felismino Charas; Inamassu, Letícia Rocha; Rahal, Sheila Canevese; Mamprim, Maria Jaqueline; de Castro Martins, David José; Ferro, Bárbara Sardela; da Silva, Bruna Martins; Ferreira, Gustavo Manea; Branco, Marina Paivo; Silva Júnior, José Ivaldo de Siqueira (Acta Scientiae Veterinariae, 2018)
Background: In Veterinary Medicine, there are several methods for early and accurate assessment of blood flow dynamics. The Dopplerfluxometry can access the peak systolic velocity, mean velocity and end diastolic velocity, including Resistive Index and Pulsatility Index. Normal values of Dopplerfluxometry in healthy dogs allow the identification of vascular abnormalities and authors’ knowledge there are no reference regarding the values of Dopplerfluxometry of the femoral artery in healthy dogs. The aim of the study was to assess the femoral Dopplerfluxometry of adult healthy dogs by Resistive Index, Pulsatility Index, systolic and diastolic velocities, and femoral artery diameter.Materials, Methods & Results: Eighteen healthy intact beagle dogs, male and female, aging from 2 to 4 years old (mean ± SD: mean 3 ± 0.8 years), weighing from 10.1-17.9 kg [22.3-39.5 lb] [mean ± SD: 14.3 ± 2.7 kg (31.5 ± 5.96 lb)] were used. The dogs underwent to physical examination, complete blood cell count, serum biochemistry examination urinalysis, and radiographs examination, muscular and cardiac evaluation. Females had to be in anestrous. All dogs were submitted to right femoral artery Dopplerfluxometry. The dogs were positioned in dorsal recumbency by one person without any chemical restraint. A high definition ultrasound device equipped with a 3 - 13 MHz multi-frequency linear transducer was used. The right femoral artery was identified with the transducer positioned transversely on the right triangle femoral area. Peak systolic velocity, end-diastolic velocity was measured. The Resistivity Index and Pulsatility Index were calculated automatically by the ultrasound machine software. Three measurements were obtained with the Doppler spectrum. The values of peak systolic velocity, end-diastolic velocity, Resistivity Index, Pulsatility Index and femoral artery diameter were expressed as Mean ± Standard Deviation (SD).Discussion: No studies regarding to femoral artery Dopplerfluxometry in healthy dogs were found in the ...